El papel de las dinámicas familiares en el consumo de sustancias psicoactivas y procesos de recaía de jóvenes del municipio de zarzal (V). (2024)
The objective of this research is to investigate family dynamics in the consumption of psychoactive substances and relapse processes in young people in the municipality of Zarzal (v). The conceptual approach includes family theories, references to psychoactive substances and types of consumption. A qualitative methodology was used whose information was obtained through a semi-structured interview, applied to four (4) participants, who had in their family group a member with psychoactive substance consumption problems. The results indicate that adolescence is where the risk of starting consumption increases. Regarding family factors, it was found that the use of inconsistent norms and rules and the absence of authority figures favor situations of relapse and poor adherence to treatments by young consumers.